Influence of Blanching Time on the Phytochemical and Nutritive Value of Cowpea (Vigna unguiculata L. Walp) Leafy Vegetable - M. Y. Maila; P. E. Tseke (International Journal of Food Science)
Seasonal production limits the effective utilization of cowpea, which is regarded as food and a cash income crop in most African rural communities. To reduce the bacterial content and inactivate the naturally occurring enzymes that could induce undesirable changes during storage of the vegetable, blanching is applied. However, loss in flavor and nutritional value is experienced. Therefore, a study was conducted to investigate the effects of different blanching times on cowpea at a constant temperature, on its nutritive value. A 2 kg sample of fresh leaves was divided into four portions and blanched at 95°C for 0 (control), 2.5, 5, and 10 min. The study was arranged in a completely randomized design in triplicate. Collected data included moisture, total phenolic, antioxidant activity, and minerals [calcium (Ca), potassium (K), cobalt (Co), chromium (Cr), and silicon (Si)]. Compared to the control, total phenolic increased at 2.5 min to 9.83 mg GAE/g but then decreased by 4.99 and 4.60 mg GAE/g at 5 and 10 min of blanching time, respectively. Similarly, antioxidant activity increased at 2.5 min to 1025 μg AAE/g of WM, but reduced by 751.71 and 641.80 μg AAE/g of WM at 5 and 10 min, respectively. Ca increased at 2.5, 5, and 10 min by 69.10, 62.47, and 74.53 mg/L, respectively. Similarly, K increased at 2.5, 5, and 10 min by 31.57, 49.13, and 46.03 mg/L, respectively. Contrarily, Co decreased by 7.65, 7.37, and 9.29 mg/L at 2.5, 5, and 10 min of blanching, respectively. Similarly, Cr also decreased at 2.5, 5, and 10 min, by 0.23, 0.35, and 0.56 mg/L, respectively. Si increased at 2.5 and 10 min by 4.15 and 3.31 mg/L and reduced at 5 min by 1.61 mg/L. Therefore, blanching time of 2.5 min at a constant temperature of 95°C increased the tested nutritive elements, except for moisture, Co, and Cr.